A day that shook the world (London : BBC, 1995)
A fascinating historical programme featuring 60 of the major events that have shaped the history of the 20th century - each subject is covered in 3 minutes bites combining authority and accessibility for the viewer in 3 videos
Copy available in DVD format
Keywords: World history; World politics